Normalisation of citation impact in economics - Bornmann, Lutz; Wohlrabe, Klaus (Scientometrics, 2019)
This study is intended to facilitate fair research evaluations in economics. Field- and time-normalisation of citation impact is the standard method in bibliometrics. Since citation rates for journal papers differ substantially across publication years and Journal of Economic Literature classification codes, citation rates should be normalised for the comparison of papers across different time periods and economic subfields. Without normalisation, both factors that are independent of research quality might lead to misleading results of citation analyses. We apply two normalised indicators in economics, which are the most important indicators in bibliometrics: (1) the mean normalised citation score (MNCS) compares the citation impact of a focal paper with the mean impact of similar papers published in the same economic subfield and publication year. (2) PP top 10 % is the share of papers that belong to the 10% most cited papers in a certain subfield and time period. Since the MNCS is based on arithmetic averages despite skewed citation distributions, we recommend using PP top 10 % for fair comparisons of entities in economics. In this study, we apply the normalisation methods to 294 journals (including normalised scores for 192,524 papers). We used the PP top 10 % results for assigning the journals to four citation impact classes. Seventeen journals have been identified as outstandingly cited. Two journals, Quarterly Journal of Economics and Journal of Economic Literature , perform statistically significantly better than all other journals. Thus, only two journals can be clearly separated from the rest in economics.